Intensive, personalized multimodal rehabilitation in patients with primary or revision total knee arthroplasty: a retrospective cohort study - Jesper Bie Larsen; Lisbeth Mogensen; Lars Arendt-Nielsen; Pascal Madeleine (BMC, 2020)
Abstract Background Recent evidence has shown that many patients suffer from persistent pain and impaired function after primary or revision total knee arthroplasty (TKA). Post-surgical complications may in addition decrease physical performances and lead to more pain and impacted quality of life. The purpose of the study was to assess the changes in pain intensity and functional capacity among patients with post-surgical complications after TKA three weeks of intensive, personalized multimodal rehabilitation. Methods A retrospective cohort study consisting of 217 patient of which 166 had primary TKA and 51 had revision TKA was conducted. On average, primary TKA patients and revision TKA patients were 3.7 and 2.7 months post-surgical, respectively. All patients have had post-surgical complications and were referred to an inpatient rehabilitation department, where they received a personalized three-week intensive, multimodal rehabilitation protocol. The rehabilitation consisted of sessions targeting neuromuscular function, postural control, and flexibility, sessions focusing on improving muscle strength and cardiovascular function and sessions with focus on gait retraining. The frequency of training was 2-4 sessions/day. The primary outcome was the Knee injury and Osteoarthritis Outcome Score (KOOS) and secondary outcomes were pain intensities measured using numerical rating scale, 6 min. walking test, stair-climbing test and range of motion for knee flexion and extension. Outcome measures were assessed at baseline upon referral and at follow-up before discharge. Results All outcomes, except pain at rest in the revision group, improved significantly. KOOS subscales, improved 8.5 to 14.2 in the primary TKA group (p < 0.001) and 6.9 to 10.8 in the revision group (p < 0.001). For the TKA group, effect sizes were medium-to-large for all KOOS subscales, 6 min. walking test, stair-climbing test, and pain intensity during activity. For the revision group, effect sizes were medium-to-large for KOOS subscales symptoms and activity of daily living, 6 min. walking test, stair-climbing test, and knee flexion. Conclusion Patients with post-surgical complications after primary or revision TKA experienced clinical relevant improvement in self-reported outcomes, pain relief, and improved physical performances after three weeks of personalized multimodal rehabilitation. The results suggest that an intensive, multimodal approach might be useful to obtain clinically relevant improvements.